2021
DOI: 10.1038/s41396-021-00940-y
|View full text |Cite
|
Sign up to set email alerts
|

Locally adapted gut microbiomes mediate host stress tolerance

Abstract: While evidence for the role of the microbiome in shaping host stress tolerance is becoming well-established, to what extent this depends on the interaction between the host and its local microbiome is less clear. Therefore, we investigated whether locally adapted gut microbiomes affect host stress tolerance. In the water flea Daphnia magna, we studied if the host performs better when receiving a microbiome from their source region than from another region when facing a stressful condition, more in particular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 85 publications
(100 reference statements)
3
29
0
Order By: Relevance
“…Analysis of the recipient microbiomes showed that selection of bacterial groups was also stressor dependent, with a stronger selection of bacterial strains in the Microcystis and combi treatment in Daphnia that received a natural microbial inoculum, as shown in the beta diversity analysis. This is conform as suggested in Macke et al (2017Macke et al ( , 2020 and Houwenhuyse et al (2021).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Analysis of the recipient microbiomes showed that selection of bacterial groups was also stressor dependent, with a stronger selection of bacterial strains in the Microcystis and combi treatment in Daphnia that received a natural microbial inoculum, as shown in the beta diversity analysis. This is conform as suggested in Macke et al (2017Macke et al ( , 2020 and Houwenhuyse et al (2021).…”
Section: Discussionsupporting
confidence: 91%
“…Body size, in addition, was lower for individuals exposed to Aspergillus compared with the control, whereas the opposite was observed for the total number of brood. Trade-offs between survival and body size under stress were previously found in Daphnia (Adamczuk 2010 and other organisms (Sterck et al 2006, Mogensen andPost 2012) with Houwenhuyse et al (2021) suggesting a role of the microbiome for this trade-off under Microcystis stress. Here, we did, however, not find support for such a trade-off.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The gut microbiome is considered the host second genome, which emerged as a key determinant of many aspects including the capability of shaping developmental, physiological and reproductive phenotypes ( 5 ), the enhancement of feed digestibility and nutrient absorption throughout the digestive tract ( 2 ), and the inhibition on intestinal pathogenic bacteria ( 6 ). Further, unlike other environmental factors, the microbiomes may be transmitted between generations carrying the potentiality to alter traits beyond the limits of the host's genetics ( 7 ), and further worked on shaping the phenotypes of the progenies.…”
Section: Introductionmentioning
confidence: 99%
“…Further, unlike other environmental factors, the microbiomes may be transmitted between generations carrying the potentiality to alter traits beyond the limits of the host's genetics ( 7 ), and further worked on shaping the phenotypes of the progenies. Previous studies showed that gut microbiome is highly malleable by environmental factors ( 5 ) while symbiotic bacteria can increase bioavailable nutrient pools ( 7 ), which ultimately benefited the growth of the eukaryotic host.…”
Section: Introductionmentioning
confidence: 99%